What Do We Really Know About the Effects of Mindfulness-Based Training in the Workplace?. Issue 4 (17th December 2015) - Allen, Tammy D.; Eby, Lillian T.; Conley, Kate M.; Williamson, Rachel L.; Mancini, Victor S.; Mitchell, Melissa E.
Abstract : In an attempt to distill what we know about the effects of workplace mindfulness-based training, Hyland, Lee, and Mills (2015 ) cast a wide net with regard to the array of studies included in their review. For example, they include studies that investigate the benefits associated with workplace mindfulness training (e.g., Wolever et al., 2012 ) as well as training conducted for patients within primary care settings (e.g., Allen, Bromley, Kuyken, & Sonnenberg, 2009 ). In addition, their review includes studies based on self-reports of individual differences in mindfulness traits/skills (e.g., Hafenbrack, Kinias, & Barsade, 2014 ). Reviewing a broad cross-section of research is helpful to illustrate the wide-ranging nature of mindfulness research but also has the potential to obfuscate what we know about mindfulness as it pertains to workers and workplaces.